Interdisciplinary Therapy for patients with dementia - Maysa Luchesi Cera; Daniela Cristina Carvalho de Abreu; Rosângela de Abreu Venancio Tamanini; Amanda Carla Arnaut; Patrícia Pupin Mandrá; Carla da Silva Santana (Dementia & Neuropsychologia)
Patients with dementia require rehabilitation involving several health professionals, where interdisciplinary care can further enhance the routine of patients and their families.OBJECTIVE:To compare the functional performance of elderly with dementia before and after an interdisciplinary intervention program provided by a healthcare service of medium complexity.METHODS: Three cases with clinically-confirmed dementia enrolled on an interdisciplinary rehabilitation program were reported. The following instruments were applied: Mini Mental-State Exam, Clinical Dementia Rating, Geriatric Depression Scale, Lawton & Brody Index, and the Functional Independence Measure for adults (FIM). The therapeutic strategies were individualized and designed based on patient performance on the FIM, according to the criteria of the Classification of Functionality, Disability and Health, implemented at the house of therapy of the Center for Integrated Rehabilitation together with provision of guidance.RESULTS: A reduction in functional dependence was observed after intervention, evidenced by less supervision needed to carry out Activities of Daily Living. Conclusion: The three patients benefited from the interdisciplinary intervention.